Multihazard weather risk perception and preparedness in eight countries - Keul, Alexander G.; Brunner, Bernhard; Allen, John; Wilson, Katie A.; Taszarek, Mateusz; Price, Colin; Soleima, Gary; Sharma, Sanjay; Roy, Partha; Mat Said, Aini; Abu Bakar, Elistina; Ab Kadir, Mohd Zainal Abidin; et al. (American Meteorological Society, 2018)
Weather risk perception research lacks multihazard and transcultural datasets. This hypothesis-generating study used a cognitive behavioral approach and Brunswik’s lens model for subjective risk parameters across eight countries. In Germany, Poland, Israel, the United States, Brazil, India, Malaysia, and Australia, 812 field interviews took place with a uniform set of 37 questions about weather interest, media access, elementary meteorological knowledge, weather fear, preparedness, loss due to weather, and sociodemography. The local randomized quota samples were strictly tested for sample errors; however, they cannot be considered representative for individual countries due to sample size and methodology. Highly rated subjective risks included flood, heat, tornado, and lightning. Weather fear was most prominent in the Malaysian sample and lowest in the German.